2018
DOI: 10.1175/mwr-d-17-0267.1
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic Control over Orographic Precipitation Distributions during the Olympics Mountains Experiment (OLYMPEX)

Abstract: The synoptic controls on orographic precipitation during the Olympics Mountains Experiment (OLYMPEX) are investigated using observations and numerical simulations. Observational precipitation retrievals for six warm-frontal (WF), six warm-sector (WS), and six postfrontal (PF) periods indicate that heavy precipitation occurred in both WF and WS periods, but the latter saw larger orographic enhancements. Such enhancements extended well upstream of the terrain in WF periods but were focused over the windward slop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…The time of day/year was suggested by Tachibana (1995) to have an effect upon the LPE distribution during periods of weak flow, but we found the effect to be relatively minor. A number of studies show that CBVT and similar variables modulate the distribution and intensity of orographic precipitation (e.g., Minder et al 2008;Rutz et al 2014;Purnell and Kirshbaum 2018), but we found its effect on the LPE distribution was nearly identical to that of U due to their strong correlation (Fig. 3c).…”
Section: B Environmental Conditionsmentioning
confidence: 56%
“…The time of day/year was suggested by Tachibana (1995) to have an effect upon the LPE distribution during periods of weak flow, but we found the effect to be relatively minor. A number of studies show that CBVT and similar variables modulate the distribution and intensity of orographic precipitation (e.g., Minder et al 2008;Rutz et al 2014;Purnell and Kirshbaum 2018), but we found its effect on the LPE distribution was nearly identical to that of U due to their strong correlation (Fig. 3c).…”
Section: B Environmental Conditionsmentioning
confidence: 56%
“…Even mountains of more moderate scale may produce blocking in certain synoptic situations. For example, Purnell and Kirshbaum () demonstrated for the Olympic mountains that blocking tends to occur in the air ahead of the surface warm front due to the frontal inversion aloft. As the SF scheme will be active across the globe in a range of situations, it is necessary to account for this low‐level blocking.…”
Section: The Seeder–feeder Schemementioning
confidence: 99%
“…The SF process has been shown to be responsible for producing small‐scale precipitation variability over larger mountain ranges such as the Alps (Zängl, ). By comparing quasi‐idealized simulations with and without large‐scale forcing, Purnell and Kirshbaum () demonstrated that much of the orographic precipitation enhancement produced over the Olympic Mountains in the U.S. Pacific Northwest during the passage of a number of frontal systems was due to the SF process. These two mechanisms both occur within laminar flow as a result of mechanical lifting over orography.…”
Section: Introductionmentioning
confidence: 99%
“…Zagrodnik et al (2018) analyzed gauges and disdrometers located from the coast to windward slopes during a strong AR event from 12 to 13 November 2015, in which there were large concentrations of small to medium raindrops, in addition to highly varying concentrations of large drops, suggesting both warm rain (e.g., collision-coalescence) and cold rain processes (e.g., melting). Purnell and Kirshbaum (2018) noted the presence of cold rain via an active seederfeeder process during warm frontal and sector conditions throughout OLYMPEX from the synthesis of observations and model simulations in which ''seeder'' clouds initiate precipitation growth that falls into orographically enhanced (''feeder'') clouds at lower levels (Cotton et al 2011). McMurdie et al (2018) provided further evidence of this seeder-feeder process after documenting a larger reflectivity signature above the melting layer over the windward slopes compared to the ocean throughout OLYMPEX.…”
Section: Introductionmentioning
confidence: 97%